Experimental study on axial compression buckling of glass fiber reinforced plastics solid pole with circular cross-section - Si, Jianhui; Qiu, Shixiong; Feng, Shuyang; Chen, Jiebin; Wang, Zhenshan (Advances in structural engineering, 2022)
Glass fiber reinforced plastics are widely used in civil engineering because of their advantages such as light weight, high strength, good pollution resistance, and corrosion resistance. This study investigated the buckling bearing capacity, failure characteristics, and slenderness ratios of GFRP solid bars with circular cross-sections subjected to axial compression. A total of 18 specimens were categorized into six groups. The slenderness ratios ranged from 57 to 123. It was found from experiments that the instability mode of the specimens was extreme point instability, and a bearing capacity platform phenomenon was observed when overall lateral instability occurred. The failure mode was axial and transverse tearing failure of the material in the middle of the specimen. During buckling, the tensile side was transformed from the compression of the resin matrix to tension in the fibers. The elastic modulus of glass fiber was much lower than that of the resin matrix. After tension occurred, increased deformation led to a rapid increase in lateral bending, which resulted in the phenomenon of the bearing platform. At ultimate deformation, brittle failure of the specimen occurred. The buckling load of the specimen decreased sharply with an increase in the slenderness ratio, and stress ratios decreased from 34.95% to 6.73%. It is suggested that the slenderness ratio not exceed 80. Finally, based on experimental results, a practical method for calculating the stable bearing capacity of solid GFRP poles is proposed.